Global stability analysis of lifted diffusion flames. (September 2017) - Mancini, C.; Farano, M.; De Palma, P.; Robinet, J.C.; Cherubini, S.
Abstract: This work describes the development of a method for the global hydrodynamic stability analysis of diffusion flames. The low-Machnumber (LMN) Navier–Stokes (NS) equations for reacting flows are solved together with a transport equation for the mixture fraction describing the local composition of the fluid. The equations are solved by the spectral-element code NEK5000 with Legendre polynomial reconstruction of degree twelve and second-order accurate Runge-Kutta time integration scheme. In order to compute the base flow for the stability analysis, a selective frequency damping approach has been employed. The global stability analysis has been performed by a matrix-free time-stepper algorithm applied to the LMN-NS equations, using an Arnoldi method to compute the most unstable modes. Moreover, a numerical linearization of the governing equation is employed, which allows one to study the stability of diffusion flames without the direct evaluation and storage of the linearized operator. Therefore, a remarkable reduction of the storage capacity is achieved and a more flexible numerical approach is obtained. The numerical model has been validated by comparison with the results for the axisymmetric diffusion flame available in the literature.